Redeployment of the trainee orthopaedic surgeon during COVID-19: a fish out of water?. (25th September 2020) - Faria, Giles; Tadros, Baha John; Holmes, Natalie; Virani, Siddharth; Reddy, Gaddam Kumar; Dhinsa, Baljinder Singh; Relwani, Jaikumar
Abstract : Background and purpose — COVID-19 has had a significant impact on health services and the entire healthcare sector, including trauma and orthopaedics, has been compelled to adapt. At the heart of this was the redeployment of the orthopaedic trainees to support "frontline specialties". This paper sheds light on the experience of orthopaedic trainees in redeployment. Methods — In this retrospective study, we asked orthopaedic trainees in the KSS (Kent, Surrey, Sussex) and London Deaneries to complete a survey regarding their experience in redeployment during the COVID-19 outbreak. The study took place in the Kent, Surrey, Sussex, and London regions of the United Kingdom over a period of 8 weeks from 15th of March 2020 until 15th of May 2020. The study was based at East Kent Hospitals University NHS Foundation Trust and participants were recruited from a number of secondary and tertiary care centres across the region. 120 orthopaedic trainees were contacted, working in 21 teaching hospitals. Of these, 40 trainees (30%) from 13 hospitals responded and completed the survey. Results — 50% of the surveyed trainees were redeployed to other specialties. Trainees spent varying amounts of time in the redeployed speciality and gave differing views on how comfortable they felt and how useful they felt the experience was. One-third of trainees experienced symptoms and/or tested positive for COVID-19 and the majority of these were redeployed to other specialties. Interpretation — Orthopaedic training appears to have taken a temporary back seat at this time but trainees have made a significant contribution to reinforcing key front-line specialties in the fight against COVID-19.